A new association: acute macular neuroretinopathy in acute optic neuritis. Issue 5 (13th February 2019) - Deschamps, Romain; Vasseur, Vivien; Shor, Natalia; Vignal, Catherine; Salomon, Laurence; Gout, Olivier; Mauget‐Faÿsse, Martine
Abstract: Background: Acute optic neuritis (AON) is a common optic nerve disease leading to retrograde degeneration of optic nerve axons, reflected by thinning of the inner retinal layers on optical coherence tomography. On the contrary, acute macular neuroretinopathy (AMN) type 2 is a rare outer retinal disorder that leads to thinning of the outer nuclear layers and is diagnosed by multimodal imaging. The aim of this study was to report a new association between these two diseases. Methods: Patients with a first episode of optic neuritis were invited to participate in a study that involved optical coherence tomography evaluation at baseline and the following 1, 3, 6 and 12 months. All the study patients underwent ophthalmologic evaluation that comprised of visual acuity, visual field and multimodal imaging as well as orbital and brain Magnetic Resonance Imaging. A diagnosis of multiple sclerosis was made according to the 2010 McDonald criteria. Results: Six of the 114 patients with acute optic neuritis also had acute macular neuroretinopathy, of whom three were positive for myelin oligodendrocyte glycoprotein antibodies (MOG‐Abs), two had relapsing–remitting multiple sclerosis and one had clinical isolated syndrome. Conclusion: Our study suggests that it is imperative to check for associated AMN in cases of AON, especially those associated with MOG‐Abs.